Strontium Uptake and Intra-Population 87Sr/86Sr Variability of Bones and Teeth—Controlled Feeding Experiments With Rodents (Rattus norvegicus, Cavia porcellus) - Weber, Michael; Tacail, Théo; Lugli, Federico; Clauss, Marcus; Weber, Katrin; Leichliter, Jennifer; Winkler, Daniela E.; Mertz-Kraus, Regina; Tütken, Thomas (Frontiers in Ecology and Evolution, 2020)
Strontium isotopes in biogenic apatite, especially enamel, are widely employed to determine provenance and track migration in palaeontology and archaeology. Body tissues record the 87Sr/86Sr of bioavailable Sr of ingested food and water. To identify non-local individuals, knowledge of the 87Sr/86Sr of a non-migratory population is required. However, varying factors such as tissue turnover rates, feeding selectivity, Sr content, digestibility of food and the ingestion of mineral dust can influence body tissue 87Sr/86Sr. To evaluate the Sr contribution of diet and water to mammalian hard tissues 87Sr/86Sr, controlled feeding studies are necessary. Here we present 87Sr/86Sr from controlled feeding experiments with two rodent species (Rattus norvegicus, Cavia porcellus). Due to the continuous and fast incremental growth of rat and guinea pig incisors (~0.1 – 0.5 mm/day), their enamel is expected to record isotopic dietary changes. For Experiment-1: Diet Switch, animals were switched from their respective supplier food to a pelleted experimental diet containing either insect-, plant-, or meat-meal and a staggered-sampling approach was used to monitor the 87Sr/86Sr changes in rat incisor enamel and bone over the course of the experiment. In Experiment-2: Basic Diets, separated cohorts (n = 6) of rats and guinea pigs were fed one of the three pelleted diets and received tap water for 54 days. While the rat incisors showed a complete tissue turnover, the slower-growing guinea pig incisors partially retained supplier diet-related isotopic compositions. In addition, one group of rats fed plant-meal pellets received Sr-rich mineral water, demonstrating that drinking water can be an important Sr source in addition to diet. Additionally, a leaching experiment showed that only a small fraction of diet-related Sr is bioavailable. Finally, in Experiment-3: Dust Addition, guinea pigs were fed pellets with and without addition of 4 % of isotopically distinct dust (loess or kaolin). Animals that received kaolin-containing pellets displayed increased enamel 87Sr/86Sr. Intra-population 87Sr/86Sr variability within each feeding group was small and thus we conclude that it should not affect interpretations of 87Sr/86Sr in provenance studies. However, the differences between bulk food and leachate 87Sr/86Sr highlight the importance of Sr bioavailability for provenance studies and Sr isoscapes.